Limitations in and Solutions for Improving the Functionality of Picture Archiving and Communication System: an Exploratory Study of PACS Professionals' Perspectives. - Alhajeri, Mona; Shah, Syed Ghulam Sarwar (Journal of Digital Imaging, 2019)
Picture Archiving and Communication System (PACS) technology is evolving leading to improvements in the PACS functionality. However, the needs and expectations of PACS users are increasing to cope with the rising demands for improving the workflow and enhancing efficiency in healthcare. The aim was to study the limitations in the current generation of PACS and solutions for improving PACS functionality. This was a longitudinal online observational study of the perspectives of PACS professionals accessed through four online discussion groups on PACS using the LinkedIn network. In this exploratory study, the methodology involved a thematic analysis of qualitative data comprising 250 online posts/comments made by 124 unique PACS professionals collected between January 2014 and December 2015. Participants were mostly male (n = 119, 96%) from the North America (n = 88, 71%). Key themes on limitations in the current generation of PACS were image transmission problems, network and hardware issues, difficulties in changing specific settings, issues in hardcoded Digital Imaging and Communication in Medicine attributes, and problems in implementing open source PACS. Main themes on solutions for improving PACS functionality were the integration of multisite PACS, multimedia for PACS, web-based PACS, medical image viewer, open source PACS, PACS on mobile phones, vendor neutral archives for PACS, speech recognition and integration in PACS, PACS backup and recovery, and connecting PACS with other hospital systems. Despite ongoing technological developments, the current generation of PACS has limitations that affect PACS functionality leading to unmet needs and requirements of PACS users, which could impact workflow and efficiency in healthcare.